1975
DOI: 10.2307/1379606
|View full text |Cite
|
Sign up to set email alerts
|

Blood Analyses of Wolf Pups and Their Ecological and Metabolic Interpretation

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 16 publications
4
32
0
1
Order By: Relevance
“…Average values obtained for albumin and phosphorus were also similar to those reported in the literature (Table 3). These values were also consistent with those described by Roletto (1993) In wild marine mammals, the concentration of glucose in the blood can vary due to age, diet, physical activity, metabolism, environmental conditions, and seasonal variation (Halloran & Pearson 1972, LeResche et al 1974, Seal et al 1975, Matula et al 1980, Colares et al 2000. In addition, a glucose increase in plasma can be the product of stress following the manipulation of animals during sampling (Seal et al 1975, LeResche et al 1974, Hyvarinen et al 1975, Koopman et al 1995.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Average values obtained for albumin and phosphorus were also similar to those reported in the literature (Table 3). These values were also consistent with those described by Roletto (1993) In wild marine mammals, the concentration of glucose in the blood can vary due to age, diet, physical activity, metabolism, environmental conditions, and seasonal variation (Halloran & Pearson 1972, LeResche et al 1974, Seal et al 1975, Matula et al 1980, Colares et al 2000. In addition, a glucose increase in plasma can be the product of stress following the manipulation of animals during sampling (Seal et al 1975, LeResche et al 1974, Hyvarinen et al 1975, Koopman et al 1995.…”
Section: Discussionsupporting
confidence: 89%
“…These values were also consistent with those described by Roletto (1993) In wild marine mammals, the concentration of glucose in the blood can vary due to age, diet, physical activity, metabolism, environmental conditions, and seasonal variation (Halloran & Pearson 1972, LeResche et al 1974, Seal et al 1975, Matula et al 1980, Colares et al 2000. In addition, a glucose increase in plasma can be the product of stress following the manipulation of animals during sampling (Seal et al 1975, LeResche et al 1974, Hyvarinen et al 1975, Koopman et al 1995. In the present study, glucose concentration was on average higher during both study periods (Tables 1 and 3), in comparison with the California sea lion, which is the otariid species most closely related to O. flavescens with available data (Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…The physiologic basis for these comparisons is that blood chemistry of captive individuals is usually similar to blood chemistry of free-ranging individuals (Seal et al, 1975;Fuller et al, 1985). However, the physiologic status of wild-caught animals could differ from the physiologic status of captive animals, for technical reasons such as type of anesthesia, capture method, and time to blood collection, or for ecologic reasons associated with survival under natural conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The values reported by SEAL et al (1975) were converted to 51 units to make comparison easier. , the value found in our study is higher than that reported by SEAL et al (1975), o the value found in our study shows little difference from that reported by SEAL et al (1975), , the value found in our study is markedly lower than that reported by SEAL et al (1975).…”
Section: 7mentioning
confidence: 99%
“…The finding of .significantly lower values for the red blood picture in young than in adult wolves is in keeping with the observations in dogs by 5 c h a I m et al (1975) who reported that erythrocyte count, haematocrit and haemoglobin content rose steadily in dogs from 2 months of age, reaching adult values in animals aged I to 2 years. The difference in leukocyte count is not mentioned by 5 c h a I m (1975) but is listed in the roster The values reported by SEAL et al (1975) were converted to 51 units using conversion coefficients according to JAGOS and BOUDA (1981).…”
Section: 7mentioning
confidence: 99%